The effect of H3O+ on the membrane morphology and hydrogen bonding of a phospholipid bilayer - Deplazes, Evelyne; Poger, D.; Cornell, B.; Cranfield, C. (2018)
© 2018, International Union for Pure and Applied Biophysics (IUPAB) and Springer-Verlag GmbH Germany, part of Springer Nature. At the 2017 meeting of the Australian Society for Biophysics, we presented the combined results from two recent studies showing how hydronium ions (H3O+) modulate the structure and ion permeability of phospholipid bilayers. In the first study, the impact of H3O+ on lipid packing had been identified using tethered bilayer lipid membranes in conjunction with electrical impedance spectroscopy and neutron reflectometry. The increased presence of H3O+ (i.e. lower pH) led to a significant reduction in membrane conductivity and increased membrane thickness. A first-order explanation for the effect was assigned to alterations in the steric packing of the membrane lipids. Changes in packing were described by a critical packing parameter (CPP) related to the interfacial area and volume and shape of the membrane lipids. We proposed that increasing the concentraton of H3O+ resulted in stronger hydrogen bonding between the phosphate oxygens at the water–lipid interface leading to a reduced area per lipid and slightly increased membrane thickness. At the meeting, a molecular model for these pH effects based on the result of our second study was presented. Multiple µs-long, unrestrained molecular dynamic (MD) simulations of a phosphatidylcholine lipid bilayer were carried out and showed a concentration dependent reduction in the area per lipid and an increase in bilayer thickness, in agreement with experimental data. Further, H3O+ preferentially accumulated at the water–lipid interface, suggesting the localised pH at the membrane surface is much lower than the bulk bathing solution. Another significant finding was that the hydrogen bonds formed by H3O+ ions with lipid headgroup oxygens are, on average, shorter in length and longer-lived than the ones formed in bulk water. In addition, the H3O+ ions resided for longer periods in association with the carbonyl oxygens than with either phosphate oxygen in lipids. In summary, the MD simulations support a model where the hydrogen bonding capacity of H3O+ for carbonyl and phosphate oxygens is the origin of the pH-induced changes in lipid packing in phospholipid membranes. These molecular-level studies are an important step towards a better understanding of the effect of pH on biological membranes.